Dynamism in policy-affiliated transition intermediaries. (May 2022) - Talmar, Madis; Walrave, Bob; Raven, Rob; Romme, A. Georges L.
Abstract: Transition intermediaries are actors that support socio-technical transition processes by bridging structural deficiencies in a transitioning domain. Previous research has identified what roles transition intermediaries perform and how. However, while transitioning domains are by definition in a state of change, the dynamics of transition intermediaries have hardly been studied. Therefore, we explore what mechanisms are driving change in transition-supportive roles of intermediaries, and what kind of conditions enable an intermediary to be dynamically adaptive in supporting a transitioning domain. These questions are addressed in a longitudinal case study of a major European intermediary in sustainable energy. We find this intermediary changed its transition support activities as a result of the frontline staff continually exploring the needs of transition stakeholders and designing new value offerings in response. These role dynamics are enabled by a structure where the policy principal delegates the choice of support activity and external accountability to the intermediary, which organizes itself in a customer-oriented manner. As such, we conclude that the dynamics in intermediaries' transition activities arise from the interplay between policy mandate, organizational structure/design and staff agency. Highlights: The dynamics in the activities of transition intermediaries are not well understood. We present a longitudinal case study of a major sustainable energy intermediary. The intermediary continually designs new offerings in response to stakeholder needs. Dynamism arises from an interplay of policy mandate, management, and staff agency.